(untitled) (CONTINUIDAD Y DISCONTINUIDAD EN EL ESPACIO IBEROAMERICANO, 2026)
The opossum (tlacuache), the thief of fire in pre-Hispanic mythology and a cunning hero in indigenous culture, is the American Prometheus whose animality stands in contrast to European anthropocentrism. Perceived as a zoological curiosity by sixteenth-century Europeans, opossums were stripped of their mythical renown and denigrated, in Western eyes, to the status of harmful pests, despised much like rats. While the opossum of oral tradition survives both in children's literature and, humanized, in vagabonds, street vendors (most notably the blind Goyo Yic in Miguel Ángel Asturias's Men of Maize), and other figures of urban subculture, new avatars of this genuinely American marsupial have recently emerged in several novels by Mexican authors (e.g., Emmanuel Peña and Jacobo Santoyo), at the same time that the ecological movement highlights its importance for the environment and biodiversity.